PERTANGGUNGJAWABAN APARAT DESA DALAM PENGELOLAAN DANA DESA MENURUT UNDANG-UNDANG NOMOR 6 TAHUN 2014 (Studi Di Desa Karangrejo Kecamatan Ngasem Kab. Kediri) - Ahla, Ahmad; Fathurrahman, Shalahuddin (Universitas Islam Kadiri, 2023)
The Village Fund is a fund sourced from the State Revenue and Expenditure Budget designated for the Village which is transferred through the district/city Regional Budget and Expenditure and is used to fund governance, implementation of development, community development, and community empowerment. Methods The data analysis technique used in this study was descriptive qualitative analysis. Later, this research will draw conclusions using the deductive method, namely concluding research problems briefly and clearly, starting from things that are general to things that are specific. Based on the research results presented in the previous chapter, the following conclusions can be drawn: 1) The procedures for the use, utilization and planning of village fund management by the Karangrejo Village Government Apparatus are in accordance with the provisions of Law Number 6 of 2014 and Permendagri No. 113 of 2014 related to financial management. 2) Accountability for managing village funds has also been in accordance with statutory principles by using the principles of planning, administration, distribution, accountability and reporting that is accountable and transparent. 3) Supervision efforts from the implementation of the allocation of village funds have been supervised by the BPD, Regional Government, Village Facilitators, BPK and the local community as partners and policy controllers in the allocation of village funds in Karangrejo Village, Ngasem District, Kab. Kediri.